Meckel syndrome with omphalocele and cleft lip (2014)
The Meckel Gruber syndrome is a lethal , rare and autosomal disorder. It is characterized by multiple malformation s, among these the triad of occipital encephalocoele, large polycystic kidneys an d post-axial polydactyly. A case with multiple malformations, including the less frequent as omphalocele, hypospadias and cleft lip is presented.